Synthesis and characterization of flavonoid laurate esters by transesterification. Issue 1 (4th November 2012) - Bridson, James H.; Grigsby, Warren J.; Main, Lyndsay
Abstract Laurate esters of catechin and condensed tannins were synthesized by both transesterification and conventional acylation techniques. Transesterification was developed as an alternative route to prepare flavonoid fatty acid esters as a prerequisite to advancing potential applications. Resorcinol, catechin, and two condensed tannins were transesterified with vinyl esters, and the resulting products were compared to those formed with lauroyl chloride. The esterified products, including catechin pentalaurate, were characterized both chemically and thermally. Transesterification produced partially substituted derivatives, with a preference for substitution at the catechol ring. Melt features were identified at or below 50°C, which were dependent upon the level of substitution. In addition, the tannin laurates showed thermal stability to at least 100°C and moderate retention of antioxidant properties. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013